Are Increasing Test Scores in Texas Really a Myth? - Toenjes, A.; Dworkin, A. Gary (Education Policy Analysis Archives, 2002)
Pass rates by Texas tenth-graders on the high school exit exam improved from 52 percent in 1994 to 72 percent in 1998. In his article "The Myth of the Texas Miracle in Education" (EPAA, August 2000) Professor Walt Haney argued that some part of this increased pass rate was, as he put it, an illusion. Haney contended that the combined effects of students dropping out of school prior to taking the 10th grade TAAS and special education exemptions accounted for much of the increase in TAAS pass rates. Relying on the same methodology and data that Haney used, we demonstrate that his conclusion is incorrect. None of the 20 percent improvement in the TAAS exit test pass rate between 1994 and 1998 is explained by combined increases in dropout rates or special education exemptions.